Perilaku Konsumen Dalam Penggunaan Produk Kosmetika Tidak Berizin Badan Pengawas Obat Dan Makanan (BPOM) - Fidellya Gisella Tya Andini (CV. ITTC INDONESIA, 2025)
The development of the beauty industry in Indonesia has led to increased consumption of cosmetic products, including those without a BPOM license. These illegal products remain in demand due to lower prices, beauty trends, and the influence of social media and influencers, despite their health risks. This study aims to analyze the social, economic, and psychological factors that influence consumer behavior in choosing illegal cosmetics and evaluate the effectiveness of existing regulations. The method used is a qualitative approach with empirical juridical method through legal analysis, interviews, and observations. The results show that social pressure and media trends are more dominant than awareness of product safety. Economic factors also play a role, while weak supervision exacerbates the circulation of illegal cosmetics. In conclusion, more effective education and strict supervision are needed to increase legal awareness and consumer protection of cosmetic products.